2001
DOI: 10.1023/a:1013239805915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of introduction and exclusion of large herbivores on small rodent communities

Abstract: Effects of introduction and exclusion of large herbivores on small rodent communities Smit, R.; Bokdam, J.; Ouden, J. den; Olff, H.; Schot-Opschoor, H.; Schrijvers, M. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…These results are consistent with those of Giuliano and Homyack (2004) who also studied meadow voles, and with Smit et al (2001) and Evans et al (2006) who observed field voles (Microtus agrestis (L., 1761)), an European species, that occupies an ecological niche similar to that of the meadow vole in North America. This avoidance of grazed sites may be due to the decrease in vegetation cover associated with cattle grazing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with those of Giuliano and Homyack (2004) who also studied meadow voles, and with Smit et al (2001) and Evans et al (2006) who observed field voles (Microtus agrestis (L., 1761)), an European species, that occupies an ecological niche similar to that of the meadow vole in North America. This avoidance of grazed sites may be due to the decrease in vegetation cover associated with cattle grazing.…”
Section: Discussionsupporting
confidence: 91%
“…Small rodents are excellent study organisms because their rapid reproductive cycles allow for observing rapid responses in population density to environmental perturbations. Most studies investigating the impacts of cattle grazing on small mammals obtained results that varied greatly according to the system and region that were being studied (Grant et al 1982;Hayward et al 1997;Matlack et al 2001Matlack et al , 2001Steen et al 2005;Oksanen et al 1999;Tabeni and Ojeda 2005;Damhoureyeh and Hartnett 1997;Smit et al 2001;Evans et al 2006). Owing to this variation, two main hypotheses in the ecological literature are commonly put forward to explain the effects of cattle grazing on the behaviour and ecology of small-rodent species: (1) a decrease of vegetation increases predation risk and thus population density (Kotler 1984;Kotler and Blaustein 1995) and (2) the quality and quantity of vegetation available is influenced by cattle grazing and thus strongly influences habitat use of small rodents (Arsenault and Owen-Smith 2002) and their performance and persistence on the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the existence of indirect interactions between rodents versus ungulates and wild boars may be responsible for an increase in the rodent populations due to fencing (Focardi et al 2000;Smit et al 2001;Shepherd and Ditgen 2005;Muñoz and Bonal 2007). Although in our model the shrub cover explained only 0.44% of the total variance, this may be attributed to operational sampling restrictions (same shrub cover for the six species on each sampling station and for both years).…”
Section: Landscape Unit Selectionmentioning
confidence: 76%
“…Deer herbivory can determine the structure and composition of forest herb layers, subcanopy and ultimately forest canopies through their impacts on regeneration, generally with an increase in unpalatable species or those resistant to browsing (Kirby 2001;Horsley et al 2003;Joys et al 2004;Rooney et al 2004;Stone et al 2004;Focardi and Tinelli 2005;Gill and Fuller 2007). In turn, this can have cascade effects on biodiversity, including songbird abundance and species composition (McShea and Rappole 2000;Berger et al 2001;Fuller 2001;Allombert et al 2005a;Gill and Fuller 2007), nest predation rates (Martin and Joron 2003), the abundance and density of invertebrates (Baines et al 1994;Allombert et al 2005b;Hegland et al 2005) and the abundance and seed predation activity of small mammals (Flowerdew and Ellwood 2001;Smit et al 2001). England: major impacts on woodland herb layer composition and tree regeneration 14,28,29,30 References: 1: Moriarty (2004); 2: Hall and Gill (2005); 3: Wilson et al (2006); 4: SCI (2006); 5: Flueck et al (2003); 6: Veblen et al (1989); 7: Veblen et al (1992); 8: Relva and Veblen (1998); 9: Husheer et al (2003); 10: Ueckermann and Hansen (1994); 11: Gebhardt (1996); 12: Fraser et al (2000); 13: Lever (1985); 14: Joys et al (2004); 15: Putman et al (1989); 16: …”
Section: Ecosystem Impacts Of Native and Introduced Speciesmentioning
confidence: 99%